Theologian of the Resurrection : N.T. Wright's Eschatology and Mission Theology - Kramer, E. J. David, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
In this study, N.T. Wright's exceptional work on the resurrection is shown to form the centre of his eschatology and mission theology. Wright's emphasis on the historicity of Jesus' resurrection for the gospel's missional encounter with the West is highlighted. By drawing out the significance of the resurrection for Wright's eschatological narrative, the author sets the stage for Wright's mission theology, focusing on the church, evangelism, political theology, and eschatological ethics. Wright's emphasis on doing history is explained in terms of the theological conviction that, since God acted in history, historical study has become a sphere of missional engagement.